The Concept of Frugal Living in the Qur'an: Muhammad Hasbi Ash-Shiddieqy's Perspective in Tafsir An-Nur - Julaikha, Siti; Ahmad Zainuddin; Amir Mahmud (Jurnal Semiotika-Q, 2025)
In the current era that emphasizes a consumptive and hedonistic culture, a simple lifestyle as a wise use of resources is very important. This study aims to examine Islamic teachings through the interpretation of the Qur'an which provides guidelines for the wise use of wealth, avoiding wasteful behavior, emphasizing the balance between meeting individual needs, and upholding social benefits. In other words, this study discusses the concept of frugal living in the Qur'an which is focused on the study of Tafsir An-Nur by Muhammad Hasbi Ash-Shiddieqy. This research uses qualitative methods and types of library research with descriptive-analytical techniques. Thus, the results show that according to Hasbi Ash-Shiddieqy, frugal living in the Qur'an leads to a balanced, wise life event, while still paying attention to spiritual and social welfare. Hasbi's perspective emphasizes a simple life that prioritizes important needs and always gets closer to Allah, and shares with others. The contribution of the results of this study can add and foster efforts to apply the principles of frugal living in modern life to achieve sustainable welfare both from an economic, social and environmental point of view. In the current era that emphasizes a consumptive and hedonistic culture, a simple lifestyle as a wise use of resources is very important. This study aims to examine Islamic teachings through the interpretation of the Qur'an which provides guidelines for the wise use of wealth, avoiding wasteful behavior, emphasizing the balance between meeting individual needs, and upholding social benefits. In other words, this study discusses the concept of frugal living in the Qur'an which is focused on the study of Tafsir An-Nur by Muhammad Hasbi Ash-Shiddieqy. This research uses qualitative methods and types of library research with descriptive-analytical techniques. Thus, the results show that according to Hasbi Ash-Shiddieqy, frugal living in the Qur'an leads to a balanced, wise life event, while still paying attention to spiritual and social welfare. Hasbi's perspective emphasizes a simple life that prioritizes important needs and always gets closer to Allah, and shares with others. The contribution of the results of this study can add and foster efforts to apply the principles of frugal living in modern life to achieve sustainable welfare both from an economic, social and environmental point of view.